One-step Laparoscopic and Endoscopic Treatment of Gallbladder and Common Bile Duct Stones: Our Experience of the Last 9 Years in a Retrospective Study. Issue 12 (December 2013) - Liverani, Andrea; Muroni, Mirko; Santi, Francesco; Neri, Tiziano; Anastasio, Gerardo; Moretti, Marco; Favi, Francesco; Solinas, Luigi
The optimal timing and best method for removal of common bile duct stones (CBDS) associated with gallbladder stones (GBS) is still controversial. The aim of this study is to investigate the outcomes of a single-step procedure combining laparoscopic cholecystectomy (LC), intra-operative cholangiography (IOC), and endoscopic retrograde cholangiopancreatography (ERCP). Between January 2003 and January 2012, 1972 patients underwent cholecystectomy at our hospital. Of those, 162 patients (8.2%; male/female 72/90) presented with GBS and suspected CBDS. We treated 54 cases (Group 1) with ERCP and LC within 48 to 72 hours. In 108 patients (Group 2) we performed LC with IOC and, if positive, was associated with IO-ERCP and sphincterotomy. In Group 1, a preoperative ERCP and LC were completed in 50 patients (30%). In four cases (2%), an ERCP and endobiliary stents were performed without cholecystectomy and then patients were discharged because of the severity of clinical conditions and advanced American Society of Anesthesiologists score (III to IV). Two months later a preoperative ERCP and removal of biliary stents were performed followed by LC 48 to 72 hours later. In Group 2, the IOC was performed in all cases and CBDS were extracted in 94 patients (87%). In two cases, the laparoscopic choledochotomy was necessary to remove large stones. In another two cases, an open choledochotomy was performed to remove safely the stones with T-tube drainage. In three cases, conversion was necessary to safely complete the procedure. The mean operative time was 95 minutes (range, 45 to 150 minutes) in Group 1 and 130 minutes (range, 50 to 300 minutes) in Group 2. The mean hospital stay was 6.5 days (range, 4 to 21 days) in Group 1 and 4.7 days (range, 3 to 14 days) in Group 2. Five cases (two in Group 2 and three in Group 1) presented with CBDS at 12 to 18 months after surgery. They were treated successfully with a second ERCP. There was no perioperative mortality. Our experience suggests that when clinically and technically feasible, a single-stage approach combining LC, IOC, and ERCP to the patients diagnosed with chole-choledocholithiasis is indicated. The IO-ERCP with CBDS extraction is a safe and effective method with low risk of postoperative pancreatitis. One-step treatment is more comfortable for the patient and also reduces the mean hospital stay.